Neuropsychological Tests in Post-operative Cognitive Dysfunction: Methods and Applications - Liu, Jun; Huang, Kequn; Zhu, Binbin; Zhou, Bin; Ahmad Harb, Ahmad Khaled; Liu, Lin; Wu, Xiang (Frontiers in Psychology, 2021)
Postoperative cognitive dysfunction (POCD) is a neurological complication that mostly occurs in older people after anesthesia/surgery, with varying durations and significant differences in the severity of cognitive impairment. POCD is mainly manifested by memory loss, accompanied by abnormal emotions, behaviors and language, mostly without consciousness disorder. The clinical performance of POCD lacks specificity but can reflect the severity of cognitive impairment in patients. The diagnosis of POCD can not be separated from the evaluation of patients' perioperative cognitive function, and the more popular and accepted method is neuropsychological tests (NPTs).